Analisis Film Kill The Messenger Dalam Representasi Kode Etik Jurnalistik (Analisis Semiotika Ferdinand De Saussure) - Masagus Achmad Fahrel; Indrawati; Jufrizal (CV. ITTC INDONESIA, 2024)
This thesis is entitled Analysis of the Film Kill The Messenger in the Representation of the Journalistic Code of Ethics (Semiotic Analysis of Ferdinand De Saussure). Kill The Messenger is a film with crime, thriller, biographical genre that released on October 10 2014, directed by Michael Cuesta. This film is set in the United States, when a controversial scandal was revealed involving the United States government in drug trafficking involving rebel groups in Central America. The purpose of this research is to determine the meaning of the journalistic code of ethics in the film Kill The Messenger through signifiers and signifieds, as well as the application of the Press Council's Journalistic Code of Ethics (KEJ) by journalists in the film Kill The Messenger. This research uses a qualitative method with Ferdinand De Saussure's semiotic approach. The types of data used are primary and secondary. Data collection uses observation and documentation methods. The results of this research conclude that the semiotic meaning of the journalistic code of ethics can be built through signifiers and signifieds, then researchers found that the Press Council's Code of Journalism Ethics (KEJ) was implemented.